Analisis Yuridis Kredit tanpa Agunan dalam Hubungan Hukum Antara Bank dan Debitur - Septina Rahmi Kinasih; Dwi Atmoko (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
Unsecured Credit (Kredit Tanpa Agunan/KTA) is a banking loan facility granted without collateral, where the legal relationship between the bank and the debtor is established through a credit agreement governed by the Indonesian Civil Code and banking regulations. The absence of collateral shifts the primary guarantee to the debtor’s creditworthiness and good faith, thereby increasing the importance of the prudential principle and thorough credit analysis. This juridical study analyzes the legal basis of unsecured credit, bank mechanisms for mitigating default risk, and the legal consequences arising from such credit arrangements. Particular attention is given to the use of standard form credit agreements and their compliance with consumer protection principles, especially regarding transparency, fairness of contractual clauses, and the determination of interest rates and penalty provisions. The study finds that adequate legal safeguards are necessary to prevent imbalance between the parties and to ensure legal certainty, fairness, and protection for both banks and debtors within the framework of modern banking practices